2018
DOI: 10.1080/02703181.2018.1520381
|View full text |Cite
|
Sign up to set email alerts
|

Validated Fall Risk Assessment Tools for Use with Older Adults: A Systematic Review

Abstract: Aims: to find and describe, through a systematic review, validated assessment tool that evaluate the fall risk in older adults. Methods: MEDLINE, PEDro, CINAHL, and PsycINFO were consulted and no restrictions were applied to the year or country of publication but the searches were limited to studies published in English. Two authors independently identified eligible studies on the basis of inclusion criteria and extracted data. Results: Fifty-five eligible studies were identified, out of which 33 valued risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 71 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…R.O.M.A. association in the last few years has dealt with several systematic reviews and the validation of many outcome measures in Italy (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Methodsmentioning
confidence: 99%
“…R.O.M.A. association in the last few years has dealt with several systematic reviews and the validation of many outcome measures in Italy (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that the NAHS is considered a good instrument for the evaluation of young and active patients with hip disease. NAHS is a good instrument in clinical practice and in research studies because it is very simple, self-administered and quick to complete (only 5 minutes) and to understand for a maximum compliance of the patient and it is specific for young and physically active individuals [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The research group was composed of medical doctors and rehabilitation professionals from the Sapienza University of Rome and from the Rehabilitation and Outcome Measure Assessment (ROMA) Association, which conducted the study (14,15,(24)(25)(26)(27)(28)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%